Evaluation of the relative accuracy of anthropometric indicators to assess body fatness as measured by air displacement plethysmography in Indian women. Issue 5 (19th February 2016) - Varghese, Deethu Sara; Sreedhar, S.; Balakrishna, N.; Venkata Ramana, Y.
Abstract : Objective: To assess the relative accuracy of anthropometric indicators of body fatness or adiposity as compared to the percent fat measured by air displacement plethysmography in Indian women with normal body mass index (BMI). Methods: Percent body fat was assessed using the BodPod in 58 women, aged 30–56 years. The relative accuracy of anthropometric indicators of body fatness like BMI, waist‐stature‐ratio (WSR), waist‐thigh‐ratio (WTR), waist‐hip‐ratio (WHR), and circumferences at arm, neck, chest, waist, hip, and thigh were tested using an ROC curve analysis. Results: Seventy‐nine percent women had excess body fat (≥30%). Among the 10 indicators tested, BMI and arm circumference (AC) demonstrated high accuracy (AUC > 0.9) to assess body fatness with derived cutoffs of 21.2 kg/m 2 and 24.2 cm, respectively. WSR and circumferences at neck, chest, waist, hip, and thigh showed moderate accuracy to assess body fatness, whereas WHR and WTR demonstrated poor accuracy. Conclusions: BMI and AC were the best performing indicators of adiposity among the indicators studied. AC, being a single measurement, is practical and a good choice. Am. J. Hum. Biol. 28:743–745, 2016. © 2016 Wiley Periodicals, Inc.